2022
DOI: 10.1002/adfm.202108883
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Self‐Assembly Driven Nucleus‐Targeted Photo‐Immune Stimulator with Chromatin Decompaction Function for Robust Innate and Adaptive Antitumor Immunity

Abstract: Efficient nuclear DNA damage and release is highly recommended to improve the photodynamic immunotherapy by eliciting innate immune response yet remains challenging. Herein, an intracellular self-assembly driven nucleustargeted photo-immune stimulator (PIS) with chromatin decompaction function is reported for innate and adaptive antitumor immunity co-activation. The PIS consists of vorinostat (SAHA)-loaded manganese-porphyrin metal-organic framework (Mn (III)-TCPP MOF) with further modification of AS1411 aptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Currently, increasing emphasis is being placed on the use of certain stress agents that might elicit ICD in tumor cells [ 47 ]. Recent studies have shown that PDT can elicit an adaptive immune response by inducing ICD, thereby expanding the mechanism of PDT in clinical therapy [ 48 ]. It is necessary to explore whether the oxidative stress caused by PDT-GT drives immunological responses of tumor cell immunogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, increasing emphasis is being placed on the use of certain stress agents that might elicit ICD in tumor cells [ 47 ]. Recent studies have shown that PDT can elicit an adaptive immune response by inducing ICD, thereby expanding the mechanism of PDT in clinical therapy [ 48 ]. It is necessary to explore whether the oxidative stress caused by PDT-GT drives immunological responses of tumor cell immunogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al developed an intracellular self-assembly driven nuclear-targeted and harmless switchable photoimmunostimulator (PIS) composed of a vorinostat (SAHA)-loaded Mn-porphyrin MOF (Mn (III)-TCPP MOF) and further surface modification composition of PEI and AS1411 aptamers. 178 Benefiting from the quenching effect of Mn (III) on TCPP, PIS exhibited low phototoxicity during blood circulation. AS1411 could promote the uptake of PIS by tumor cells through active targeting, and then PIS was decomposed into Mn 2+ , TCPP, SAHA and AS1411 under the action of intracellular GSH.…”
Section: ■ Structures Of Mn-based Nanocarriersmentioning
confidence: 99%
“…By constructing an in vivo bidirectional 4T1 tumor model and an antimigration model, it was demonstrated that the synthesized MnO x NSs could effectively inhibit primary/distal tumor growth and tumor metastasis (Figure c). Shi et al developed an intracellular self-assembly driven nuclear-targeted and harmless switchable photoimmunostimulator (PIS) composed of a vorinostat (SAHA)-loaded Mn-porphyrin MOF (Mn (III)-TCPP MOF) and further surface modification composition of PEI and AS1411 aptamers . Benefiting from the quenching effect of Mn (III) on TCPP, PIS exhibited low phototoxicity during blood circulation.…”
Section: Application For Ros-mediated Tumor Therapymentioning
confidence: 99%
“…Many studies have revealed that the electrostatic interactions between short nucleic acids (such as siRNA or DNA aptamers) and cell penetrating peptides or amphiphilic peptides can promote the formation of a stable complex and cellular uptake. [25][26][27][28][29][30] Thus, PDCs can also take advantage of positively charged peptides to achieve nucleic acid drug delivery through DNA-peptide selfassembly by electrostatic interactions. As a result, remarkable synergistic effects of nucleic acid drugs and PDC on cancer proliferation inhibition are observed.…”
Section: Introductionmentioning
confidence: 99%